(untitled) (Research, Society and Development, 2022)
Introduction: Duchenne muscular dystrophy (DMD) is a genetic pathology that generates changes in the x gene. Muscle changes will occur, progressively and irreversibly. Its physical signs and symptoms are: decrease in muscle mass, presence of muscle contractures, decrease in muscle strength, and abnormality in muscle tone. Objective: To demonstrate how physical therapy works in the treatment of DMD patients. Methodology: This study is a qualitative, descriptive and exploratory literature review, based on scientific articles directly related to the proposed theme. The descriptors were used: duchenne syndrome; physiotherapy, health. Published scientific articles covering the period from 2017 to 2022, in Portuguese and English, were used. The bibliographic survey was carried out in the following database: Scielo, Pubmed, Google academic, books and published works. Results: It is a degenerative and disabling genetic disease that affects only boys. Its main characteristic is the progressive degeneration of the muscle, due to the absence of a protein. Conclusion: This study demonstrated how Duchenne syndrome affects its patients, the signs and symptoms, the main physical and muscular affections in these patients. The physiotherapeutic interventions in the treatment of (DMD) were analyzed, being reported in the work the main specific techniques, for the treatments, the resources used, maneuvers and exercises. Work is important, as it portrays the role of the physiotherapist in the treatment of Duchenne syndrome, the methods and techniques used in the treatment, the importance of physiotherapy in the treatment of (DMD) has been increasing.